Comparison of three "acute:chronic" workload ratio methods to monitor professional rugby union players` workload as a function of positions during pre-season period - Ren, X.; Boisbluche, S.; Demy, M.; Ding, S.; Prioux, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The quantification of workload (WL) is based primarily on forwards and backs in rugby union (RU)1, necessitating a more refined division to clarify the function of each position. In addition, as a common method of analyzing data in team sports2, no scientific research has reported to quantify the variability of all acute chronic workload ratio (ACWR) models in pre-season training for RU. Therefore, this paper aims (i) to investigate the differences in external workload (EWL) of players at five positions after eight weeks, (ii) to compare the variations in ACWR for players at various positions, as well as (iii) to analyze the substitutability of the three ACWR approaches in professional RU players.